eCM 2017
DOI: 10.22203/ecm.v034a01
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the bioactive makeup of demineralised dentine matrix on bone marrow mesenchymal stem cells for enhanced bone repair

Abstract: Dentine matrix has proposed roles for directing mineralised tissue repair in dentine and bone; however, the range of bioactive components in dentine and specific biological effects on bone-derived mesenchymal stem cells (MSCs) in humans are less well understood. The aims of this study were to further elucidate the biological response of MSCs to demineralised dentine matrix (DDM) in enhancing wound repair responses and ascertain key contributing components. Dentine was obtained from human teeth and DDM proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 18 publications
3
46
0
1
Order By: Relevance
“…The amount of growth factors was detected by enzyme-linked immunosorbent assay (ELISA). Results showed that TGF-β1 was the most abundant growth factor; BMP-2, FGF-2, VEGF, PDGF and IGF-1 demonstrated intermediate abundance; while BMP-4 and BMP-7 had the lowest concentrations, as shown in Table 1 [32]. DDM proposed osteogenic and dentingenic differentiation of bone mesenchymal stem cells (BMSCs), however, after fractionation of growth factors from DDM by heparin affinity chromatography, the osteogenic responses of BMSCs diminished, indicated that growth factors play significant role in the osteogenesis and dentingenesis of DDM.…”
Section: Demineralized Dentin Matrix (Ddm) Microstructurementioning
confidence: 98%
See 1 more Smart Citation
“…The amount of growth factors was detected by enzyme-linked immunosorbent assay (ELISA). Results showed that TGF-β1 was the most abundant growth factor; BMP-2, FGF-2, VEGF, PDGF and IGF-1 demonstrated intermediate abundance; while BMP-4 and BMP-7 had the lowest concentrations, as shown in Table 1 [32]. DDM proposed osteogenic and dentingenic differentiation of bone mesenchymal stem cells (BMSCs), however, after fractionation of growth factors from DDM by heparin affinity chromatography, the osteogenic responses of BMSCs diminished, indicated that growth factors play significant role in the osteogenesis and dentingenesis of DDM.…”
Section: Demineralized Dentin Matrix (Ddm) Microstructurementioning
confidence: 98%
“…The demineralization process opens the dentin tubules and frees up the growth factors, which can stimulate tissue repair and regeneration. Previous studies demonstrated transforming growth factor β (TGF-β1), bone morphogenetic proteins (BMPs), vascular endothelial growth factor (VEGF), fibroblast growth factor-2 (FGF-2), platelet-derived growth factor (PDGF) and insulin-like growth factor-1 (IGF-1) in DDM [32][33][34][35][36]. The amount of growth factors was detected by enzyme-linked immunosorbent assay (ELISA).…”
Section: Demineralized Dentin Matrix (Ddm) Microstructurementioning
confidence: 99%
“…35 Among many NCPs preembedded in the dentin inorganic mineral phase, 15,36,37 HD-GFs, including transforming GF b, BMP-2, fibroblast growth factor, vascular endothelial growth factor, platelet-derived GF, BMP-7, and BMP-4, have been extensively studied. 19 BMP-2, BMP-7, and BMP-4 are present in dentin as ED-BMPs.…”
Section: Histological Observationsmentioning
confidence: 99%
“…This feature could be explained by the observation that dentin and bone are similar in chemical composition and structural organization, both showing collagen and mineral crystal deposition at the micro-and nanometer levels. Moreover, dentin has an absolute number of NCPs, including dentin sialoprotein, osteopontin, dentin matrix protein-1, and matrix extracellular phosphoglycoprotein, 18,19 which are thought to influence cell behavior. 39 For example, osteocytic proteins, which are expressed in bone but not in dentin, may suppress osteoclast formation during the bone remodeling process.…”
Section: Osteoclast Activation With Rhbmp-2mentioning
confidence: 99%
See 1 more Smart Citation